Gender Diversity and Generational Gaps: Two Hurdles Worth One Giant Leap - Renee Marine (Academic Chairpersons Conference Proceedings, 2020)
Presenter and participants will explore the gender and generational similarities and differences that exist today both in the classroom and departmentally. Emerging strategies and best practices will be shared and discussed.
Keywords: Leadership; Gender Diversity; Generational Gaps; Department culture